СРАВНИТЕЛЬНЫЙ АНАЛИЗ ФЛОРИСТИЧЕСКИХ КОМПОНЕНТОВ МЕЖДУ ОСТРОВОМ “ВОЗРОЖДЕНИЕ” И ПРИЛЕГАЮЩИМИ ТЕРРИТОРИЯМИ - Султамуратов, А.Т.; Тамамбетова, Ш.Б.; Адилов, Б.А.; Полвонов, Ф.И.; Шарипова, В.К. (SCIENCE and SOCIETY, 2024)
The article examines the flora of Vozrozhdeniya Island, located in the southern part of the Aral Sea. As a result of the study, it was found that the flora of the island is a characteristic example of desert plant communities and flora.